ON THE OVARIAN EGGS OF BENTHOSEMA FIBULATUM AND B. PTEROTUM (MYCTOPHIDAE) FROM NORTHERN ARABIAN SEA - Hussain, S M; Khan, J Ali (Indian Journal of Fisheries, 2011)
Reports on the fish assessment in the Arabian sea (Anon., 1975; 1976; 1977) indicate abundant myctophid catches (upto a maximum 20,000 kg per hour of trawling). The abundant myctophid species belonged to genus Benthosema, of which two species B. fibulatum and J?. pterotum are dominant. The eggs and larvae of the two species were abundant among oceanic plankton in December, 1964-April, 1965 (Nellen, 1973).